Socially responsible IT management - Erbschloe, Michael, 1951- (Burlington, MA : Digital Press, 2003)
Socially Responsible IT Management shows IT professionals how to overcome the social crisis that has resulted from the wide-spread use of information technology. By responsibly managing security threats, protecting individual privacy, reducing hazardous waste, and minimizing other negative effects on IT staff and computer users, as well as ordinary citizens around the world, IT professionals can benefit the society at large and reap rewards for their own organizations as well. Scandals at Enron, Andersen, Sotheby's and Christie's, Merrill Lynch, and Tyco are fueling a crisis of confidence in business. Regulators, voters, investors, customers, and employees are demanding that businesses be more socially responsible. Rhetoric is not enough, all organizations need to demonstrate that they are living up to social expectations. Erbschloe shows managers how to take charge of key aspects of their IT operations and follow a morally, ethically, and legally correct path to success. Supported by author speaking tour and "Computer Economics" website, www.computereconomics.com Step-by-step instructions on how to accomplish objectives of privacy and security Explains principles of ergonomics, energy efficiency, and recycling that can bring return on investment.
An overview of socially responsible information technology management -- Principle 1, Appropriately staff IT departments -- Principle 2, Fairly compensate IT workers -- Principle 3, Adequately train computer users -- Principle 4, Provide ergonomic user environments -- Principle 5, Maintain secure and virus-free computer systems -- Principle 6, Safeguard the privacy of information -- Principle 7, Ethically manage intellectual property -- Principle 8, Utilize energy-efficient technology -- Principle 9, Properly recycle used computer equipment -- Principle 10, Support efforts to reduce the digital divide -- Organizing for socially responsible information technology management -- The future of socially responsible information technology management.
Includes index.
Keywords: Information technology; Social responsibility of business; Business enterprises -- Computer networks; Business -- Data processing; Electronic books